Finite element modeling of reinforced concrete structural walls - Güllü, Muhammet Fetih. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
This study was conducted to propose a two dimensional finite element model to obtain the inelastic response of reinforced concrete (RC) structural walls under generalized reversed-cyclic, in-plane loading conditions. The proposed model in this study incorporates a fixed crack angle modeling approach, which is suitable for reversed cyclic loading conditions and a feasible candidate for two dimensional finite element modeling methodology. The main purpose of this study is to capture a reasonable prediction of unexpected shear yielding and nonlinear shear deformations in slender walls. The analytical model was shown to capture, with reasonable accuracy, overall behavioral attributes of RC structural walls, including cyclic lateral load versus shear distortion, lateral stiffness, strength and ductility. Nonlinear force-deformation response of the analytical model also represents cyclic response properties; including stiffness degradation, plastic (residual) displacements, and pinching behavior. The proposed finite element model was implemented into Matlab and analyses were performed using a drift-controlled nonlinear analysis solution strategy. Comparison of the analytical and experimental model results was conducted and reasonably well results were obtained for slender walls. For checking the sensitivity of the analytical model results to modeling parameters, parametric sensitivity studies were conducted. Modeling parameters related to the number of model elements, axial force level, web reinforcement ratio and wall slenderness ratio were changed to demonstrate the sensitivity of the proposed model to important response parameters.
Keywords: Finite element method.